Pt-mo-nfg catalyst and preparation method and application thereof
Patent Information
- Application Number
- CN202611381724.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]为克服现有Pt基乙醇氧化催化剂活性不足、抗CO中毒能力弱、稳定性差的技术缺陷,本发明提供了一种Pt-Mo-NFG催化剂及其制备方法与应用
本发明通过氟掺杂精准调控铂纳米颗粒与氮氟共掺杂石墨烯载体之间的强金属-载体相互作用,并协同单原子钼的催化作用,所得Pt-Mo-NFG催化剂中Pt2+含量显著提高,XPS分析显示可达45.7%,有利于优化催化剂的电子结构,在乙醇氧化反应中表现出极高的质量活性(2151.94mA·mg-1),约为商业Pt/C催化剂的7.2倍。而且通过对比实验可以得到,未引入氟掺杂的Pt-Mo-NG催化剂在活性和稳定性上均显著低于本发明催化剂。本发明实现了对金属-载体相互作用的精准调控,为乙醇燃料电池提供了高性能、高稳定性的阳极催化剂,具有突出的技术进步和实用价值。
Smart Images

Figure CN122889773A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of methods for directly converting chemical energy into electrical energy, and particularly to catalysts for ethanol fuel cells, specifically a Pt-Mo-NFG catalyst and its preparation method and application. Background Technology
[0002] Direct ethanol fuel cells (DEFCs) are considered highly promising portable and mobile power sources due to the advantages of ethanol, such as high energy density, wide availability, and ease of storage and transportation. However, the commercialization of DEFCs is severely limited by the sluggish kinetics of its anodic ethanol oxidation reaction (EOR). EOR is a complex process involving twelve electron transfers, involving not only multi-step dehydrogenation of ethanol but, more importantly, the breaking of the C-C bonds in the ethanol molecule to achieve complete oxidation. If the C-C bonds cannot be effectively activated, the reaction will stop at the stage of partial oxidation products such as acetic acid or acetaldehyde, resulting in a significant reduction in fuel utilization. In addition, intermediates such as CO generated during EOR are strongly adsorbed onto the active sites of the catalyst, leading to catalyst poisoning and deactivation.
[0003] Platinum (Pt)-based materials are recognized as the most active EOR catalysts to date, but they still face core challenges such as limited C / C bond breaking ability and susceptibility to CO intermediate poisoning. To overcome these limitations, existing modification strategies mainly include alloying, structural regulation, and support engineering. Among these, nitrogen-doped carbon (NG) is widely used as a support for Pt-based catalysts due to its high conductivity, large specific surface area, and strong metal-support interaction (SMSI). However, single N doping has limitations in regulating the electronic structure of the carbon framework and enhancing SMSI, making it difficult to simultaneously achieve high dispersion of Pt nanoparticles, optimized electronic structure, and improved C / C bond activation ability.
[0004] In contrast, dual heteroatom co-doping can more significantly modulate the electron distribution, defect density, and surface chemical environment of carbon supports, thereby enabling more precise control over the electronic structure of the supported metal. Fluorine (F), as the most electronegative element, is expected to further promote charge transfer between the support and the metal. In the Pt–Mo–NFG (fluorine-nitrogen co-doped carbon-supported platinum-molybdenum) system, Mo provides abundant Mo–OH active sites, rapidly oxidizing and removing toxic intermediates such as CO from the Pt surface, significantly improving anti-poisoning ability and cycling stability. Secondly, Mo lowers the d-band center of Pt through electronic regulation, weakening the adsorption strength of Pt–CO; simultaneously, it acts as an anchoring site to inhibit Pt aggregation, increasing the electrochemical active area and mass activity. Currently, research on the preparation of PtMo-based catalysts with synergistic regulation by fluorine-nitrogen doping and their application in EOR is insufficient, especially the technical scheme using atomic layer deposition as the main preparation method, which is rarely addressed in existing technologies. Summary of the Invention
[0005] To overcome the technical defects of existing Pt-based ethanol oxidation catalysts, such as insufficient activity, weak resistance to CO poisoning, and poor stability, this invention provides a Pt-Mo-NFG catalyst, its preparation method, and its application.
[0006] This invention provides a Pt-Mo-NFG catalyst, comprising a substrate and an active structure supported on the substrate. The substrate is an NFG substrate, and the active structure is a platinum-molybdenum active structure, which consists of platinum nanoparticle active centers and molybdenum single-atom active sites. The platinum-molybdenum active structure is formed by sequentially depositing MoO2 on the NFG substrate through atomic layer deposition. X Deposition layer and PtO X The deposited layer is then reduced to obtain the final product. The average particle size of the platinum nanoparticles is 2.5–4.0 nm, preferably 3.0–3.5 nm. Molybdenum is uniformly dispersed in the form of single atoms or atomic clusters on the NFG substrate and the surface of the platinum nanoparticles. Compared to a single NG substrate, the NFG substrate has a higher lattice defect density and a richer layered wrinkle structure, which is beneficial for providing more metal anchoring sites and improving electron transport.
[0007] Preferably, the NFG substrate is prepared by mixing and grinding NG and NH4F, annealing and calcining under an argon atmosphere, washing and drying, wherein the mass ratio of NG to NH4F is 1:2~4, the heating rate of annealing and calcining is 4~6℃ / min, the holding temperature of calcination is 600~800℃, and the calcination time is 0.5~2h. More preferably, the mass ratio of NG to NH4F is 1:3, the heating rate of annealing and calcining is 5℃ / min, the calcination temperature is 700℃, and the calcination time is 1h.
[0008] Preferably, in the platinum-molybdenum-based electrocatalytic ethanol oxidation catalyst, the mass percentage of Pt is 5-15%, more preferably 9-12%; and the mass percentage of Mo is 0.1-2.0%, more preferably 0.3-0.8%. In a preferred embodiment, the mass percentage of Pt is about 10.56%, and the mass fraction of Mo is about 0.5%.
[0009] Preferably, MoO X Deposition layer and PtO X The reduction of the deposited layer is carried out in an argon-hydrogen mixed atmosphere with a volume ratio of Ar to H2 of 46:4, a reduction temperature of 200-300℃, and a reduction time of 0.5-1.5 h. More preferably, the reduction time is 1 h.
[0010] Preferably, the platinum in the active center of the platinum nanoparticles has a valence of 0 (Pt). 0 ) and divalent (Pt) 2+Both forms coexist, with divalent platinum accounting for 40-60% by mass, more preferably 42-47%; molybdenum at single-atom active sites coexists in tetravalent, pentavalent, and hexavalent forms. Higher Pt... 2+ The ratio helps to enhance the adsorption capacity for oxygen-containing intermediates, thereby promoting the oxidative removal of toxic species such as CO.
[0011] This invention also provides a method for preparing a Pt-Mo-NFG catalyst, comprising the following steps: Step S1: Mix and grind GO and melamine in a certain mass ratio. Place the mixture in a tube furnace and heat it to 600-900℃ at a heating rate of 1-10℃ / min under an inert atmosphere. Hold the temperature for 0.5-2h and then cool, wash and dry to obtain nitrogen-doped graphene, denoted as NG. Preferably, the inert atmosphere is argon, the heating rate is 5℃ / min, the temperature is raised to 800℃, and the temperature is held for 1h. Step S2: NG and NH4F are mixed and ground in a certain mass ratio. The mixture is placed in a tube furnace and heated to 600-800°C at a heating rate of 1-10°C / min under an inert atmosphere. The mixture is then held at this temperature for 0.5-2 hours. After cooling, the mixture is washed and dried to obtain nitrogen-fluorine co-doped graphene, denoted as NFG. Preferably, the inert atmosphere is argon, the heating rate is 5°C / min, the temperature is raised to 700°C, and the mixture is held at this temperature for 1 hour. Step S3: The NFG obtained in step S2 is uniformly dispersed in an ethanol solution to obtain a suspension with a concentration of 0.01 g / mL. The suspension is uniformly coated on the surface of a quartz plate, dried, and then placed in a vacuum reaction chamber to obtain an NFG substrate. The temperature of the reaction chamber is 170~270℃, the pressure is 10~200 Pa, and the carrier gas is filled at a volume ratio of 1:5~50 to the vacuum reaction chamber. The carrier gas flow rate is fixed during the deposition process. Preferably, the temperature of the reaction chamber is 180℃, the pressure is 80 Pa, and the carrier gas is filled at a volume ratio of 1:6 to the vacuum reaction chamber. Step S4: On the NFG substrate surface, using molybdenum hexacarbonylMo(CO)6 as the molybdenum precursor and ozone (O3) as the oxidant, alternately pulse Mo(CO)6 and O3 at a reaction temperature of 180℃. The pulse time for a single cycle of Mo(CO)6 is 0.5–2 s, the exposure time is 5–10 s, and the purging time is 20–40 s; the pulse time for a single cycle of O3 is 0.2–1 s, the exposure time is 5–10 s, and the purging time is 20–40 s. This cycle is repeated 50–150 times to obtain MoO. X / NFG intermediate; preferably, the pulse time of a single cycle of Mo(CO)6 is 1s, the exposure time is 8s, and the purging time is 30s, and the pulse time of a single cycle of O3 is 0.5s, the exposure time is 8s, and the purging time is 30s; the number of cycles of deposition is preferably 100; the specific pulse time, exposure time and purging time can be adjusted according to the existing technology and actual conditions.
[0012] Step S5, the MoO obtained in step S4 X On the surface of the / NFG intermediate, using trimethylplatinum MeCpPtMe3 as the platinum precursor and ozone (O3) as the oxidant, alternating pulses of MeCpPtMe3 and O3 were performed at a reaction temperature of 200–300 °C. The pulse time for MeCpPtMe3 in a single cycle was 0.2–1 s, the exposure time was 5–10 s, and the purge time was 20–40 s. For O3, the pulse time was 0.2–1 s, the exposure time was 5–10 s, and the purge time was 20–40 s. This cycle was repeated 20–60 times to obtain PtO. X / MoO X / NFG precursor; preferably, the reaction temperature is 250℃, the pulse time for a single cycle of MeCpPtMe3 is 0.5 seconds, the exposure time is 8 seconds, and the purge time is 30 seconds, and the pulse time for a single cycle of O3 is 0.5 seconds, the exposure time is 8 seconds, and the purge time is 30 seconds; the number of deposition cycles is preferably 40; the specific pulse time, exposure time, and purge time can be adjusted according to existing technology and actual conditions.
[0013] Step S6: Take the PtO obtained in step S5. X / MoO X The NFG precursor was collected from quartz plates, ground, and placed in a tube furnace. Under an argon-hydrogen mixed atmosphere, it was annealed and reduced at 200–300 °C for 0.5–2 h to finally obtain the Pt-Mo-NFG catalyst. The preferred Ar / H2 volume ratio in the argon-hydrogen mixed atmosphere was 46:4, the preferred annealing temperature was 250 °C, and the preferred reduction time was 1 h.
[0014] Preferably, in step S3, in the vacuum reaction chamber, O3 is pulsed onto the NFG surface and pressure is maintained to oxidize and remove impurities on the NFG surface and prepare for the deposition of metal precursors; in step S4, after pulsed Mo(CO)6, air is pumped out to remove unadsorbed molybdenum precursors, and after pulsed O3, air is pumped out to remove unreacted oxidants; in step S5, after pulsed MeCpPtMe3, air is pumped out to remove unadsorbed platinum precursors, and after pulsed O3, air is pumped out to remove unreacted oxidants.
[0015] Preferably, in step S1, the mass ratio of GO to melamine is 1:1 to 10; in step S2, the mass ratio of NG to NH4F is 1:2 to 4; in step S3, the temperature of the vacuum reaction chamber is 180°C, the pressure is 80 Pa, and the volume ratio of the carrier gas to the vacuum reaction chamber is 1:6. More preferably, the mass ratio of GO to melamine is 1:5, and the mass ratio of NG to NH4F is 1:3. This invention also provides the application of the Pt-Mo-NFG catalyst described herein in the electrocatalytic oxidation of ethanol.
[0016] Preferably, the ethanol oxidation reaction occurs in a mixed electrolyte of 0.5M H2SO4 and 1M C2H5OH; the test temperature for the ethanol oxidation reaction is 10℃~30℃, the scan rate is 10~200mV / s, and the reaction system is an argon-saturated electrolyte system.
[0017] The technical solution provided by this invention has the following technical effects compared with the prior art: This invention precisely modulates the strong metal-support interaction between platinum nanoparticles and nitrogen-fluorine co-doped graphene supports through fluorine doping, and synergizes the catalytic effect of single-atom molybdenum to obtain a Pt-Mo-NFG catalyst with Pt in it. 2+ The content was significantly increased, reaching 45.7% as shown by XPS analysis, which is beneficial for optimizing the electronic structure of the catalyst and exhibiting extremely high mass activity (2151.94 mA·mg) in the ethanol oxidation reaction. -1 The activity is approximately 7.2 times that of commercial Pt / C catalysts. Furthermore, comparative experiments show that the Pt-Mo-NG catalyst without fluorine doping exhibits significantly lower activity and stability than the catalyst of this invention. This invention achieves precise control over the metal-support interaction, providing a high-performance, highly stable anode catalyst for ethanol fuel cells, demonstrating significant technological advancement and practical value. Attached Figure Description
[0018] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 The images show the SEM, EDS elemental distribution, TEM, HAADF-STEM, and HRTEM images of the Pt-Mo-NFG catalyst of Example 1 of this invention. Figure 2 This is the XRD pattern of Embodiment 1 of the present invention; Figure 3 The XPS spectra of the catalysts in Example 1 and Comparative Example 1 of this invention are shown below. Figure 4 The CV diagrams show the ethanol oxidation reactions under acidic conditions in Example 1, Comparative Example 1, and commercial Pt / C of the present invention. Figure 5 The CV diagrams are for the ethanol oxidation reaction under acidic conditions in Examples 1-7 of this invention. Detailed Implementation
[0021] To better understand the above-mentioned objectives, features, and advantages of the present invention, the solutions of the present invention will be further described below. It should be noted that, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other.
[0022] Many specific details are set forth in the following description in order to provide a full understanding of the invention, but the invention may also be practiced in other ways different from those described herein; obviously, the embodiments in the specification are only some embodiments of the invention, and not all embodiments.
[0023] The specific embodiments of the present invention will now be described in detail with reference to the accompanying drawings. Example 1
[0024] In this embodiment, the Pt-Mo-NFG catalyst has a Pt mass percentage of 10.56% and a Mo mass percentage of 0.5%. It consists of an NFG substrate and a molybdenum-platinum active structure supported on the surface of the NFG substrate. The molybdenum-platinum active structure is composed of platinum nanoparticle active centers and molybdenum single-atom active sites. The molybdenum is tetravalent, pentavalent, and hexavalent molybdenum, and the platinum is 0valent and divalent platinum.
[0025] This embodiment describes a method for preparing a Pt-Mo-NFG catalyst, comprising the following steps: Step S1: Weigh 100 mg GO and 500 mg melamine, grind and mix them evenly. Place the resulting mixture in a tube furnace, heat it to 800 °C at 5 °C / min under an argon atmosphere, hold it at that temperature for 1 hour, and then cool it naturally to room temperature to obtain nitrogen-doped graphene, denoted as NG. Step S2: Take 1g of the prepared NG powder and mix it with 3g of ammonium fluoride NH4F, and grind it thoroughly. Place the mixture in a quartz boat, put it in a tube furnace, and calcine it at 700℃ at 5℃ / min under an argon atmosphere of 70 sccm for 1 hour. After cooling, wash it three times each with ultrapure water and anhydrous ethanol, and dry it to obtain nitrogen and fluorine co-doped graphene, denoted as NFG; Step S3: Take 10 mg of NFG and uniformly disperse it on the surface of a quartz plate (spray coating with anhydrous ethanol and allow to air dry), then place it in a vacuum reaction chamber for atomic layer deposition. The temperature of the vacuum reaction chamber is 180℃, and an NFG substrate is obtained. Step S4: First, pulse the Mo precursor hexacarbonylmolybdenum Mo(CO)6 onto the surface of the NFG substrate and then expose it to allow Mo(CO)6 to adsorb onto the surface of the NFG substrate. Then, perform vacuum purging to remove the unadsorbed Mo precursor. The pulse time is 1s, the exposure time is 8s, and the purging time is 28s. Step S5: Then pulse ozone (O3) and expose to allow the oxidant to react with the Mo precursor adsorbed on the NFG surface as described in step S4. Then, remove unreacted O3 by evacuation and purging. The pulse duration is 0.5 s, the exposure duration is 8 s, and the purging duration is 25 s. Step S6: Repeat steps S4 and S5 sequentially, performing 100 deposition cycles to obtain MoO. X / NFG intermediate; Step S7: The temperature of the vacuum reaction chamber is raised to 250℃. Then, the Pt precursor trimethylmethylcyclopentadiene platinum (MeCpPtMe3) is pulsed onto the surface of the Mo-NFG substrate and then exposed to allow the Pt precursor to adsorb onto the surface of the Mo-NFG substrate. After that, the unadsorbed Pt precursor is removed by purging. The pulse duration is 0.5s, the exposure duration is 8s, and the purging duration is 25s. Step S8: Then pulse ozone and expose to allow the oxidant to react with the Pt precursor adsorbed on the NFG surface as described in step S7. Then, remove the unreacted oxidant by evacuation and purging. The pulse time is 0.5s, the exposure time is 8s, and the purging time is 25s. Step S9: Repeat steps S7 and S8 sequentially, performing 40 deposition cycles to obtain PtO. X / MoO X / NFG precursor; Step S10: PtO X / MoO X After collecting and grinding the NFG precursor, 10 mg was placed in a tube furnace and then reduced to obtain the Pt-Mo-NFG catalyst. The conditions for the reduction treatment were: 250℃, 0.1 MPa, constant temperature for 1 h, and the flow rate of the reducing gas passing through 10 mg of Pt-Mo-NFG every 1 h was 1200 mL. A 46:4 argon-hydrogen mixture was used as the reducing gas. Example 2
[0026] In this embodiment, the Pt-Mo-NFG catalyst has a Pt mass percentage of 10.56% and a Mo mass percentage of 0.5%. It consists of an NFG substrate and a molybdenum-platinum active structure supported on the NFG substrate surface. The molybdenum-platinum active structure comprises platinum nanoparticle active centers and molybdenum single-atom active sites, wherein the molybdenum is tetravalent, pentavalent, and hexavalent, and the platinum is 0valent and divalent. The preparation method of the Pt-Mo-NFG catalyst in this embodiment is basically the same as in Example 1, except that in step S2 of Example 2, the mass ratio of NG to NH4F is 1:1. Examples 3-7
[0027] The Pt-Mo-NFG catalysts in Examples 3-7 contain 10.56% Pt and 0.5% Mo by mass. They consist of an NFG substrate and a molybdenum-platinum active structure supported on the NFG substrate surface. The molybdenum-platinum active structure comprises platinum nanoparticle active centers and molybdenum single-atom active sites, with molybdenum being tetravalent, pentavalent, and hexavalent, and platinum being 0valent and divalent. The preparation methods of the Pt-Mo-NFG catalysts in Examples 3-7 are basically the same as in Example 1, with the only differences being: in Example 3, the mass ratio of NG to NH4F in step S2 is 1:2; in Example 4, the mass ratio of NG to NH4F in step S2 is 1:4; in Example 5, the mass ratio of NG to NH4F in step S2 is 1:5; in Example 6, the mass ratio of NG to NH4F in step S2 is 1:6; and in Example 7, the mass ratio of NG to NH4F in step S2 is 2:1. Example 7 can be used as a comparative example of Example 1. Comparative Example 1
[0028] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that fluorination is not performed in step S2, i.e., the NG substrate prepared above is used directly as the support without adding NH4F. The subsequent ALD deposition of molybdenum and platinum precursors and the reduction steps are exactly the same as in Example 1. The resulting catalyst is referred to as the Pt-Mo-NG catalyst.
[0029] The ethanol oxidation performance test results of the mass ratios in Examples 1-7 and Comparative Example 1 are shown in Table 1.
[0030] Table 1. Test results of acidic EOR catalytic performance of catalysts under different conditions.
[0031] The Pt-Mo-NFG catalyst in Example 1 was subjected to SEM, TEM, and HAADF-STEM tests, and the results are as follows: Figure 1 As shown. Figure 1In the middle, (a) and (b) are two SEM images of the Pt-Mo-NFG catalyst in Example 1, respectively. Figure 1 (c) shows the corresponding EDS elemental distribution of the Pt-Mo-NFG catalyst. Figure 1 Image (d) is a TEM image of the Pt-Mo-NFG catalyst in Example 1. Figure 1 In Figure (e), the HAADF-STEM image of the Pt-Mo-NFG catalyst is shown. In Figure (f), the HRTEM image of the Pt-Mo-NFG catalyst in Example 1 is shown.
[0032] Depend on Figure 1 As shown in (a) to (c), the Pt-Mo-NFG catalyst maintains a typical layered and wrinkled morphology, but the surface exhibits more obvious and irregular wrinkles, possibly due to the alteration of local carbon framework stress caused by the re-doping of F. EDS spectra show that F, N, Pt, and Mo are all uniformly dispersed in the material, with no obvious elemental segregation observed, indicating that the atomic layer deposition process achieved uniform coverage of the metal components on the support surface. Figure 1 The TEM image in (d) shows that the metal nanoparticles are uniformly dispersed on the NFG substrate without agglomeration, and the particle size is approximately 3.2 nm. Figure 1 The HAADF-STEM image in (e) shows that Mo is dispersed in single-atom form on the NFG substrate. Figure 1 The HRTEM image in (f) shows a lattice spacing of 0.223 nm for the metal particles, corresponding to the (111) crystal plane of Pt. However, due to the small size of the Mo element in the atomic layer deposition, no obvious Mo element was observed. In summary, this invention suggests that the Pt-Mo-NFG catalyst is a Pt-based catalyst in which Mo single atoms bridge Pt nanoparticles and NFG substrate, with Mo atoms uniformly distributed on the surfaces of NFG and Pt nanoparticles.
[0033] The Pt-Mo-NFG catalyst in Example 1 was subjected to XRD testing, and the XRD pattern was obtained as follows: Figure 2 As shown, two broadened diffraction peaks appear at approximately 26° and 42° in the XRD pattern, corresponding to the (002) and (100) crystal planes of graphitic carbon, indicating that the support maintains the basic layered graphite structure. Multiple distinct diffraction peaks are observed in the range of 40° to 80°, attributed to the (111), (200), and (220) crystal planes of Pt, confirming the successful loading and good crystallinity of Pt nanoparticles. No MoO2 in the Pt-Mo-NFG catalyst was observed in the XRD pattern. x The diffraction peaks indicate that Mo exists mainly in the form of clusters or atoms, which is consistent with the TEM observations.
[0034] XPS tests were performed on the catalysts in Example 1 and Comparative Example 1, and the Pt 4f spectra were obtained as follows: Figure 3 As shown, compared with the single-doped Pt-Mo-NG catalyst, the characteristic peaks of Pt 4f in the double-doped Pt-Mo-NFG catalyst all show a positive shift of approximately 0.3 eV. Peak fitting of the Pt 4f spectrum reveals four characteristic sub-peaks: the peaks at 73.1 eV and 76.5 eV correspond to the oxidized state of Pt, respectively. 2+ 4f 7 / 2 and Pt 2+ 4f 5 / 2 The peaks at 71.7 eV and 75.1 eV correspond to the metallic state of Pt. 0 4f 7 / 2 and Pt 0 4f 5 / 2 Quantitative analysis results show that Pt in the Pt-Mo-NFG catalyst... 2+ The content was 45.7%, significantly higher than that of the Pt-Mo-NG catalyst (33.0%). The slight positive shift of the Pt 4f orbital and the higher Pt content... 2+ The content indicates that F co-doping strengthens the interfacial interaction between Pt nanoparticles and the NFG substrate and promotes charge transfer. 2+ The site exhibits strong adsorption capacity for reaction intermediates, thus allowing for the regulation of oxygen-containing intermediate adsorption behavior during the EOR process in acidic media. Pt 2+ The site can bind firmly. Intermediates such as OH and CO ultimately enhance the catalytic activity of the EOR catalyst and strengthen its resistance to CO poisoning under acidic conditions.
[0035] All electrochemical tests were performed in a standard three-electrode system. The working electrode was a glassy carbon electrode with a diameter of 3 mm, the counter electrode was a platinum wire, and the reference electrode was a reversible hydrogen electrode (RHE). Before testing, the Pt-Mo-NFG catalyst was uniformly coated on the surface of the glassy carbon electrode and allowed to dry naturally before use.
[0036] Specific embodiments also disclose the application of the Pt-Mo-NFG catalyst in the electrocatalytic oxidation of ethanol. Specifically, ethanol undergoes oxidation in a mixed electrolyte of 0.5 M H2SO4 and 1 M C2H5OH under the action of the Pt-Mo-NFG catalyst described in this invention. The ethanol oxidation reaction is tested at a temperature of 10℃~30℃, a scan rate of 10~200 mV / s, and the reaction system is an argon-saturated electrolyte system.
[0037] Specifically, the electrolyte solution consists of 0.5M H2SO4 (for CO dissolution testing) and a mixed solution of 0.5M H2SO4 and 1M C2H5OH (for ethanol oxidation reaction testing). Before all tests, high-purity argon gas must be purged into the electrolyte for 30 minutes to remove dissolved oxygen, and an argon atmosphere must be maintained above the liquid surface during the test.
[0038] Preparation of the working electrode: Weigh 2 mg of the dried and ground Pt-Mo-NFG catalyst sample into a centrifuge tube, add 190 µL of distilled water and 190 µL of anhydrous ethanol, sonicate for 30 min, then add 20 µL of naphthol membrane solution, and sonicate again for 30 min to fully disperse and form a uniform suspension. During sonication, the temperature of the medium water must not exceed 35 °C. After sonication, use a pipette to draw 10 µL of the catalyst suspension and evenly drop it onto the polished, cleaned, and activated glassy carbon electrode. Allow it to air dry at room temperature for 30 min to obtain the working electrode, achieving a catalyst loading of 0.255 mg·cm³. -2 .
[0039] The formula for calculating mass activity (MA) is: MA = I / m, where I (unit mA) is the test current and m (unit mg) is the mass of Pt loaded on the glassy carbon electrode.
[0040] The ethanol oxidation reaction of Example 1, Comparative Example 1, and commercial Pt / C was tested in a mixed solution of 0.5M H2SO4 and 1M C2H5OH. Figure 4 As shown, the initial oxidation potential of the Pt-Mo-NFG catalyst is only 0.41 V, significantly lower than that of the Pt-Mo-NG catalyst (0.5 V) and commercial Pt / C (0.66 V), indicating that the strong metal-support interaction induced by fluorine doping effectively lowers the reaction energy barrier. At the peak potential, the MA of the Pt-Mo-NFG catalyst is 2151.94 mA·mg. Pt -1 Higher than Pt-Mo-NG catalyst (1104.12 mA·mg). Pt -1 ) and commercial Pt / C (299.23 mA·mg Pt -1 The improvements were 1.95 times and 7.2 times that of the Pt-Mo-NG catalyst and the commercial Pt / C, respectively. This significant improvement is mainly attributed to the fact that fluorine atom doping enhances electron transfer between Pt nanoparticles and the NFG substrate, thereby increasing the amount of Pt in the active sites. 2+ The ratio (45.7% vs. 33.0% of Pt-Mo-NG catalyst) optimizes the adsorption free energy of oxygen-containing intermediates and promotes the oxidative removal of toxic species such as CO.
[0041] Comparison of the mass activity test results of Example 1 with the performance of commercial Pt / C catalysts Figure 4 As shown.
[0042] The results of Example 1 in Table 1 and Figure 4 The results show that the Pt-Mo-NFG catalyst of the present invention has good catalytic efficiency for the EOR reaction under acidic conditions.
[0043] The Pt-Mo-NFG catalysts in Examples 1-7 were tested for ethanol oxidation in a mixed solution of 0.5 M H2SO4 and 1 M C2H5OH. The results are as follows: Figure 5 As shown, when the NG:NH4F ratio is 1:3, the Pt-Mo-NFG catalyst exhibits the highest catalytic activity at the peak potential in the acidic EOR reaction, with a maximum MA of 2151.94 mA·mg. Pt -1 .
[0044] In summary, this invention successfully prepared a Pt-Mo-NFG catalyst by precisely controlling the strong metal-support interaction between platinum nanoparticles and nitrogen-fluorine co-doped graphene supports through fluorine doping, and by synergizing the catalytic effect of single-atom molybdenum. Compared with commercial Pt / C catalysts, the catalyst of this invention exhibits significantly higher mass activity in the ethanol oxidation reaction. This invention provides a high-performance, high-stability anode catalyst for direct ethanol fuel cells, demonstrating significant technological advancement and practical value.
[0045] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the present invention. Although detailed descriptions have been provided with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.
Claims
1. A Pt-Mo-NFG catalyst, comprising a substrate and an active structure supported on the substrate, characterized in that, The substrate is an NFG substrate, and the active structure is a platinum-molybdenum active structure, which consists of platinum nanoparticle active centers and molybdenum single-atom active sites. The platinum-molybdenum active structure is formed by depositing MoO on the NFG substrate sequentially using an atomic layer deposition process. X Deposition layer and PtO X The sedimentary layer is then reduced to its original state.
2. The Pt-Mo-NFG catalyst according to claim 1, characterized in that, The NFG substrate was prepared by mixing and grinding NG and NH4F, annealing and calcining under argon atmosphere, washing and drying. The mass ratio of NG to NH4F was 1:2~4. The heating rate of annealing and calcination was 4~6℃ / min, the holding temperature was 600~800℃, and the calcination time was 0.5~2h.
3. The Pt-Mo-NFG catalyst according to claim 1, characterized in that, In the Pt-Mo-NFG catalyst, the mass percentage of Pt is 9~12% and the mass percentage of Mo is 0.3~0.8%.
4. A Pt-Mo-NFG catalyst according to any one of claims 1 to 3, characterized in that, MoO X Deposition layer and PtO X The reduction of the deposited layer was carried out in an argon-hydrogen mixed atmosphere with a volume ratio of Ar to H2 of 46:4, a reduction temperature of 200~300℃, and a reduction time of 0.5~1.5h.
5. The Pt-Mo-NFG catalyst according to claim 4, characterized in that, Platinum in the active center of platinum nanoparticles exists in both 0-valent and 2-valent forms, with 2-valent platinum accounting for 40-60% of the mass; molybdenum in the single-atom active site exists in three forms: 4-valent, 5-valent, and 6-valent.
6. A method for preparing a Pt-Mo-NFG catalyst, characterized in that, Includes the following steps: Step S1: Mix and grind GO and melamine in a certain mass ratio. Place the mixture in a tube furnace and heat it to 600-900℃ at a heating rate of 1-10℃ / min under an inert atmosphere. Hold the temperature for 0.5-2h and calcine. After cooling, wash and dry to obtain nitrogen-doped graphene, denoted as NG. Step S2: Mix and grind NG and NH4F in a certain mass ratio, place the mixture in a tube furnace, heat to 600-800℃ at a heating rate of 1-10℃ / min under an inert atmosphere, hold for calcination for 0.5-2h, cool, wash and dry to obtain nitrogen-fluorine co-doped graphene, denoted as NFG. Step S3: The NFG obtained in step S2 is uniformly dispersed in an ethanol solution to obtain a suspension with a concentration of 0.01 g / mL. The suspension is uniformly coated on the surface of a quartz plate, dried, and then placed in a vacuum reaction chamber to obtain an NFG substrate. The temperature of the reaction chamber is 170~270℃, the pressure is 10~200 Pa, and the carrier gas is filled with a volume ratio of 1:5~50 to the volume of the vacuum reaction chamber. The carrier gas flow rate is fixed during the deposition process. Step S4: On the NFG substrate surface, using Mo(CO)6 as the molybdenum precursor and O3 as the oxidant, at a reaction temperature of 180℃, alternately pulse Mo(CO)6 and O3. The pulse time for a single cycle of Mo(CO)6 is 0.5~2s, the exposure time is 5~10s, and the purging time is 20~40s; the pulse time for a single cycle of O3 is 0.2~1s, the exposure time is 5~10s, and the purging time is 20~40s. This cycle is repeated 50~150 times to obtain MoO. X / NFG intermediate; Step S5, the MoO obtained in step S4 X On the surface of the / NFG intermediate, using MeCpPtMe3 as a platinum precursor and O3 as an oxidant, alternating pulses of MeCpPtMe3 and O3 were performed at a reaction temperature of 200–300 °C. For MeCpPtMe3, the pulse time per cycle was 0.2–1 s, the exposure time was 5–10 s, and the purge time was 20–40 s. For O3, the pulse time per cycle was 0.2–1 s, the exposure time was 5–10 s, and the purge time was 20–40 s. This cycle deposition was repeated 20–60 times to obtain PtO. X / MoO X / NFG precursor; Step S6: Take the PtO obtained in step S5. X / MoO X The NFG precursor was collected from a quartz plate, ground, and then placed in a tube furnace. Under an argon-hydrogen mixed atmosphere, it was annealed and reduced at 200-300℃ for 0.5-2 hours to finally obtain the Pt-Mo-NFG catalyst.
7. The method for preparing a Pt-Mo-NFG catalyst according to claim 6, characterized in that, In step S3, in the vacuum reaction chamber, O3 is pulsed onto the NFG surface and pressure is maintained to oxidize and remove impurities on the NFG surface and prepare for the deposition of metal precursors; in step S4, after pulsed Mo(CO)6, air is pumped out to remove unadsorbed molybdenum precursors, and after pulsed O3, air is pumped out to remove unreacted oxidants; in step S5, after pulsed MeCpPtMe3, air is pumped out to remove unadsorbed platinum precursors, and after pulsed O3, air is pumped out to remove unreacted oxidants.
8. The method for preparing a Pt-Mo-NFG catalyst according to claim 7, characterized in that, In step S1, the mass ratio of GO to melamine is 1:1~10; in step S2, the mass ratio of NG to NH4F is 1:2~4; in step S3, the temperature of the vacuum reaction chamber is 180℃, the pressure is 80Pa, and the volume ratio of the carrier gas to the vacuum reaction chamber is 1:
6.
9. The application of the Pt-Mo-NFG catalyst as described in any one of claims 1 to 5 in the electrocatalytic oxidation of ethanol.
10. The application according to claim 9, characterized in that, Ethanol oxidation occurs in a mixed electrolyte of 0.5 M H2SO4 and 1 M C2H5OH. The test temperature for ethanol oxidation is 10℃~30℃, the scan rate is 10~200mV / s, and the reaction system is an argon-saturated electrolyte system.